PENEMBAKAN POLRI DALAM MELAKSANAKAN TUGAS YANG DAPAT DI KATEGORIKAN SEBAGAI PEMBELAAN TERPAKSA - Rachmadio Firmansyah; Otto Yudianto (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Members of the police force are often blamed for actions taken with spontaneity in taking an action. Forced actions taken, such as shootings, are often questioned. Whether the action should have been taken or should it have gone through a special technical technicality so that members of the police force can take decisive action by carrying out a shooting. So it is felt that there must be rules that provide protection to police members so that police members can carry out their assigned duties properly, and police members are not always blamed for actions resulting from their actions to carry out their duties. The duties carried out by police members are indeed many directly related to the community so that people's opinions on the implementation of the duties of police members are indeed diverse and not all police members who are proven to have committed criminal acts such as shootings can be criminally charged. So there needs to be a legal protection for members of the police who carry out their duties, especially taking decisive action by forcibly paralyzing even resulting in a person's death